Flood Loss Assessment - A Case Study of Dordi Basin, Gandaki, Province - Chaudhari, Satyam Kumar (Journal of Environment Sciences, 2023)
Hydropower plants are a quintessential source of clean and economical energy, serving as the primary preference for renewable energy technologies for many governments owing to their unparalleled ability to deliver dependable baseload power with negligible fluctuation. However, despite their numerous benefits, the construction and operation of these plants pose a significant threat to the population living in the river basin and the equipment involved. The damage caused by flooding can have devastating and long-lasting impacts on the area, leading to severe economic losses and a prolonged period of recovery. In the case of the Dordi Rural Municipality, a study was carried out, which revealed that the Upper Dordi Hydropower Plant Headwork and Super Dordi Hydropower Plant inlet were ravaged by a ruinous flood, which resulted in the loss of twenty million equipment and eleven workers die. The cause of the flood was attributed to the upstream landslide blockage, which eventually led to the sudden bursting of the blockage and subsequent flooding. While the compensation of the workers was provided by the District Administration Office, Lamjung, and Dordi Rural Municipality through their incurrence policy, the study underscores the urgent need to establish a highly frequent flood warning system to alert the hydropower station and the local community. Additionally, the scouring and deposition process in the river channel was observed in detail, and the data analysis indicates no significant relationship between discharge and rainfall, emphasizing the importance of proactive measures to prevent future flooding events.